Perception of parents of private school students on measles and rubella vaccination campaign in Sambalpur town - Mishra, Sanjeeb Kumar; Lakra, Kulwant; Satapathy, Durga Madhab; Panda, Sadhucharan; Pradhan, Subrat Kumar (International Journal Of Community Medicine And Public Health, 2019)
Background: In order to eliminate measles and rubella (congenital rubella syndrome) WHO has emphasized on measles and rubella (MR) vaccination campaign and India launched the ambitious MR Campaign with the help of WHO and GAVI. In Odisha the MR campaign was launched on January 29 with a target to cover nearly 1.13 crore children. The objective of the present study is to assess the knowledge of parents regarding measles and rubella infection and to identify the source of information regarding MR campaign. Methods: A cross-sectional study was conducted in Sambalpur City across 10 private schools during February 10 to March 12. Total 440 parents of children aged 5-15 years were given a questionnaire about socio-demographic characteristics, knowledge, attitudes, and behaviors towards MR Campaign. The data were collected subsequently in the next 10 days. Out of 440 parents 408 returned filled up questionnaire. Data were entered into and analyzed by using Microsoft Excel. Results: Out of the 408 respondents 362 (88.7%) parents had knowledge about MR campaign. 156 respondents was aware about importance of rubella vaccine. Parent teacher meeting (PTM) was the leading source of information for these. 388 (95%) respondent’s children had received the vaccine during campaign. Conclusions: Parent-teacher’s meeting was the main source of information. However social mobilisation such as street play, miking, rallies by school children and NGOs etc., needs to be taken up for such campaigns in future.